Students' Rating of the Activities of Scientific and Pedagogical Workers as a Tool of Student-Centered Learning - Yaroshenko, Olha (Unìversiteti ì lìderstvo, 2022)
The article emphasizes that in the context of Ukraine's entry into the European Higher Education Area, the spectrum of didactic principles is expanding, among which the principle of student-centered learning is becoming more important. Based on the principles of student-centered learning, the students are responsible not only for their learning results but also for the components that influence the results, one of which is the evaluation of the activities carried out by academic and pedagogical workers. From now students of domestic institutions of higher education are involved not only in the development, improvement and evaluation of educational programs but also in the assessment of the professional active ties of teachers. To this end, higher education institutions are developing relevant normative documents and conducting surveys like “Teachers through the eyes of students”. It is noted that the world's leading education systems have significant achievements in student evaluation of the professionalism and personal qualities of teachers, and student evaluations of teaching (SET) serve as a basis for career growth, salary increases, etc. The domestic experience of student evaluations of scientific and pedagogical workers is not so long and successful; the evaluation is being formed. As a result, some problems arise, the effective solution of which depends on the internal normative provision of the procedure for conducting student evaluation of the activities of academic and pedagogical workers, obtaining reliable results and their further impartial use. Attention is focused on the fact that the psychological aspects of the subject-subject relationship of the teacher and students affect the evaluation of scientific and pedagogical workers, therefore, its results should not be absolute, but reinforced and checked with the help of other types of evaluations. With the help of a questionnaire survey of teachers of domestic institutions of higher education, their generally trusting attitude to the results of student evaluations was found out. The need for a balanced use of foreign experience in student evaluations is emphasized. For quite a long time of using the student rating (more than 50 years), foreign universities managed to avoid a number of risks and provide student ratings with leadership positions in the evaluation of the activities of scientific and pedagogical workers. Despite this, foreign researchers disagree about the effectiveness and objectivity of student ratings due to the influence on their results of the gender bias of some students, the physical attractiveness of scientific and pedagogical workers, different motivations of students to study, etc. A conclusion was made about the importance for the students to evaluate the activities carried out by scientific and pedagogical workers as a factor in the introduction of student-centered learning, the need to study the foreign experience of student evaluations of teaching (SET) and its dissemination, but taking into account and avoiding the risks revealed in the article regarding the completeness of the reliability of student evaluations.